Transcriptome‑wide excavation and expression pattern analysis of the NAC transcription factors in methyl jasmonate- and sodium chloride-induced Glycyrrhiza uralensis - Yuan Li; Yue Shi; Zidong Zhu; Xiao Chen; Kuangwei Cao; Jiatong Li; Chunsheng Liu; Da Li (Scientific Reports)
Abstract The NAC family is among the most extensive sets of plant-exclusive transcription factors (TFs), which are crucial for various plant development and stress response processes. Although a growing number of studies have been carried out on the NAC family in different species, it has not been characterized in Glycyrrhiza uralensis. To thoroughly understand the effects of methyl jasmonate (MeJA) and sodium chloride (NaCl) inductions on NAC TFs and investigate the underlying regulatory mechanism of NAC TFs in response to MeJA and NaCl on the biosynthesis of metabolites, we used transcriptome sequencing combined with qRT‒PCR to explore differential gene expression. Comparative transcriptomic profiling by RNA sequencing (RNA-seq) revealed differentially expressed NAC TFs between MeJA/CK (Mock Control) and NaCl/CK. KEGG pathway analysis revealed that NAC TFs involved in starch and sucrose, carbohydrate, lipid, and amino acid metabolism, as well as terpenoid, polyketide, and flavonoid pathways, can regulate the MeJA- and NaCl-induced responses of G. uralensis. This research lays the groundwork for a thorough comprehension of the regulatory mechanism of NAC TFs in response to MeJA and NaCl induction and their involvement in the accumulation of secondary metabolites, which can provide a scientific basis for the cultivation of high-quality varieties of G. uralensis.